Conformational Sensitivity in Photoelectron Circular Dichroism of 3‐Methylcyclopentanone. Issue 8 (9th April 2013) - Turchini, Stefano; Catone, Daniele; Zema, Nicola; Contini, Giorgio; Prosperi, Tommaso; Decleva, Piero; Stener, Mauro; Rondino, Flaminia; Piccirillo, Susanna; Prince , Kevin C.; Speranza, Maurizio
Abstract A study of (R)‐3‐methylcyclopentanone [(R)‐3‐MCP] by photoelectron spectroscopy and photoelectron circular dichroism (PECD) is presented. The synchrotron radiation gas‐phase photoelectron spectra of (R)‐3‐MCP were measured and are discussed on the basis of different theoretical methodologies. The experimental dichroism of (R)‐3‐MCP for selected deconvoluted valence states and for the carbonyl carbon 1s core state are reported and reproduced well by calculated dispersions generated by considering the contributions of two different conformers. The theoretical dichroic parameters are calculated by employing a multicentre basis set of B‐spline functions and a Kohn–Sham Hamiltonian. Temperature‐dependent PECD studies of the HOMO state and the carbonyl carbon 1s core level allowed the separation of the contributions of each conformer by photoelectron dichroism. This new approach clearly shows how the PECD methodology is sensitive to conformational and structural changes of unoriented (R)‐3‐MCP in the gas phase, opening up new perspectives in the characterisation of chiral molecular systems.